Experimental Investigation of Self-Assembled Opal Structures by Atomic Force Microscopy, Spectroscopic Ellipsometry and Reflectometry - Alekseeva, Natalia; Cema, Grigory; Lukin, Aleksey; Pan’kova, Svetlana; Solovyev, Vladimir; Veisman, Victor; Yanikov, Mikhail (Journal of Self Assembly and Molecular Electronics, 2023)
Self-assembled opal crystals (bulk silica opals and PMMA thin opal films) have been studied by atomic force microscopy (AFM) and optical spec- troscopy. Reflectance and transmittance spectra (R(λ) and T (λ), respectively) as well as spectra of ellipsometric parameters Ψ(λ) and Δ(λ)demonstrate pronounced changes with changing the angle of light incidence. Diameters of spheres obtained from AFM-images correspond to those obtained from Bragg fit to the diffraction resonance dispersions. The band of light losses detected by ellipsometry at the spectral range of avoided band crossing of opal eigenmodes was assigned to the energy exchange between these modes